Regulasi Emosi dan Kemampuan Belajar Siswa Sekolah Dasar: Sebuah Kajian Fenomenologi - Alda Permatasari; Annasriyah Masfufah; Margaretha Herlin Pratiwi; Novi Lestari; Selly Noverina; Yulita Devi Utami; Liza Murniviyanty; Arizona Arizona (Journal of Society Counseling, 2026)
Emotion regulation is a fundamental ability that plays an important role in the success of learning processes for elementary school-aged children. This study aims to gain an in-depth understanding of elementary school students' experiences of emotion regulation and its relationship with their learning ability in the real school context. This research employed a qualitative approach with a descriptive phenomenological design. Ten fifth-grade students from SD Negeri 136 Palembang were selected purposively as main informants, along with four classroom teachers and three parents. Data were collected through in-depth interviews, participatory observation, and documentation. Data validity was ensured through source triangulation and member checking. Data analysis followed Braun and Clarke's (2022) thematic analysis technique. Three main themes were identified: (1) negative emotional experiences as barriers to learning, (2) emotion regulation strategies used by students, and (3) the role of the school and family environment in supporting emotion regulation. Emotion regulation is not merely an internal factor but a socially and contextually constructed process. Holistic interventions involving both teachers and parents are essential to optimize elementary school students' learning ability.